The Investigation and Solution of the Wind Band for Basic Training at Qingdao GeWuJuYuan Wind Band Shandong Province in Qingdao of the People’s Republic of China - Li Zhenglin (Journal of Roi Kaensarn Academi, 2024)
The instrumentation in concert bands includes three families of Western musical instruments: brass, woodwind, and percussion. The history of wind music and wind performance has been rich and diverse, yet the wind band in its modern configuration as an artistic collegiate ensemble is a relatively young concept. The purposes of this research were 1) To study the problems in the basic training for the wind band. 2) To study the effectively solve the common problems in basic training for the wind band. The samples were choosing 31 students and 30 audiences who always attending wind band concerts and having a passion for wind band performances. The results are as follow 1) The problem were poor basic training, parents and teachers being impatient for success, Lack of professional teachers; Intonation issues; Tone quality problems; Rhythm issues’; Cooperation among musicians. 2) Some solutions include: Strengthen the training of personal skills, set up a group to enhance team consciousness; Establish assessment system and urge everyone to practice.